Cooperative learning models to improve mathematical problem solving ability of high school students: A systematic review of applications, factors, and barriers - Nabila Jasmin Nanditya Henti; Sintha Sih Dewanti (Universitas Sarjanawiyata Tamansiswa, 2025)
Mathematical problem-solving skills are a key competency in 21st century education, yet many secondary school students still struggle to apply mathematical concepts to real world contexts. This study employed a Systematic Literature Review (SLR) guided by the PRISMA protocol to analyze 26 relevant national and international articles published between 2015 and 2025. Findings indicated that several cooperative learning models, particularly Think Pair Share (TPS), Group Investigation (GI), and Student Teams Achievement Divisions (STAD), effectively enhanced students’ problem-solving abilities by fostering structured collaboration, critical thinking, and peer interaction. The effectiveness of these models was influenced by internal factors such as student motivation and independence, as well as external factors including teacher facilitation, classroom management, and the use of appropriate learning media. Nonetheless, practical barriers such as limited instructional time, insufficient teacher training, and inadequate school facilities hindered optimal implementation. This study underscored the importance of teacher professional development and curriculum alignment to support the integration of cooperative strategies in mathematics education. Its primary contribution lay in systematically mapping cooperative learning models, enabling factors, and implementation challenges, offering evidence-based insights for enhancing collaborative learning practices in mathematics classrooms.